Alterações ultrassonográficas renais e vesicais de ovinos confinados e suplementados com cloreto de amônio1 - Ferreira, Danilo O.l. [UNESP] (2014)
The incidence of obstructive urolithiasis in sheep is high, especially in feedlot males, both for meat production, or the breeder of high genetic value. The urinary acidification is one of the methods for preventing this disease and can be performed efficiently with supplementation of ammonium chloride (AC) in the diet. It was used 100 male lambs, in a feedlot, crossbred (Ile de France X White Dorper), aged approximately three months. It was constituted three groups: Group 21AC (n=40) that received 400mg/kg/PV of ammonium chloride/animal/day for 21 consecutive days, the time of discontinuation of the urinary acidifiers (M3) and continued clinical follow until the end of the experiment (M6); Group 42AC (n=40), that received 400mg/kg/PV of ammonium chloride/animal/day for 42 consecutive days, Group control (n=20), that did not receive ammonium chloride throughout the experimental period. The feed consisted of total dry matter, composed of 15% ground hay and 85% concentrate, water and mineral salts ad libitum. After 14 days of adaptation to food and the environment, the moments (M) for clinical evaluation, and blood collection ultrasound examinations were performed with an interval of seven days, and M0 (immediately before the beginning of the treatment with ammonium chloride), M1 (seven days), M2 (14 days after), M3 (21 days after initiation of treatment and suspension of ammonium chloride in Group 21CA), M4 (28 days), M5 (35 days), and M6 (42 days), amounting to 56 days of feedlot. The serum urea and creatinine showed no change in renal function, although the urea was above the reference values for sheep. There were compatible ultrasound images with bladder stones and dilatation of the renal pelvis. In Group 21AC, 15% (6/40) of the animals had bladder stones; in Group 42AC 5% (2/40); and in Group control, 20% (4/20) of the lambs. It was visualized suggestive images of sediment and crystals in 31% (31/100) of examined animals. Ultrasonography allowed visualization of kidney and bladder abnormalities, which were not related to clinical symptoms of obstructive urolithiasis, appearing as an examination complement of great importance for the early detection of changes in the urinary system of sheep.